Acoustic predation in a sailfish-flying fish cloak - Promode R. Bandyopadhyay (Scientific Reports, 2023)
Abstract When a sailfish circles to corral a school of flying fish in a vortex near the ocean surface, a tiny patch of arced surface waves confined to oppositely placed 70° sectors appears dispersing coherently, but why? It is modeled that, when the fish motions stop suddenly, the corralled school compacts, the tail shed propulsion vortices touch, break and radiate the pressure released from the centrifugal vortex rotation creating an acoustic monopole. The surface-wave patch is a section of the sphere of radiation. The oppositely placed curved bodies of the sailfish and the flying fish act as concave acoustic mirrors about the monopole creating a reverberating bell-shaped cloak in between which vibrates the ear bones and bladders of the flying fish disorienting them. A cup of water firmly struck on a table induces a similar vibration of a purely radial mode. The sailfish circles around the school at a depth where the wind induced underwater toroidal motion in the vertical plane becomes negligible such that the flying fish is unable to sense the tailwind direction above, limiting the ability to swim up and emerge in the right direction to glide. Experiments confirm that the flying fish tail rigidity is too low for a quick ballistic exit, which is not called for either.